A genre-based analysis of grade 12 agricultural sciences textbook: advancing bilingual academic literacy (uhlalutyo lwencwadi yezolimo yebanga le-12: ukuphuhlisa okufundisa ngeelwimi ezimbini) - Anesipho, Kroza (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.